RNA-targeted proteomics identifies YBX1 as critical for efficient HCMV mRNA translation - Rebekah J. Dickmander; Erik M. Lenarcic; John D. Sears; Andrew E. Hale; Nathaniel J. Moorman (Proceedings of the National Academy of Sciences, 2025)
Viruses have evolved unique strategies to circumvent host control of protein synthesis and enable viral protein synthesis in the face of the host response. Defining the factors that regulate viral messenger RNA (mRNA) translation is thus critical to understand how viruses replicate and cause disease. To identify factors that might regulate viral mRNA translation, we developed a technique for identifying proteins associated with a native RNA expressed from its endogenous promoter and genomic locus. This approach uses a guide RNA to target dCas13b fused to a biotin ligase domain to a specific RNA, where it covalently labels proteins in close proximity. Using this approach, we identified multiple proteins associated with transcripts encoding the human cytomegalovirus (HCMV) IE1 and IE2 proteins and found that several associated proteins positively or negatively regulate HCMV replication. We confirmed that one such protein, the cellular Y-box binding protein 1 (YBX1), binds to HCMV immediate early mRNAs and is required for efficient viral protein expression and virus replication. Ablating YBX1 expression reduced the association of HCMV immediate early mRNAs with polysomes, demonstrating a role for YBX1 as a positive regulator of viral RNA translation. These results provide a powerful tool for unraveling RNA–protein interactions that can be used in a wide range of biological processes and reveal a role for YBX1 as a critical regulator of HCMV immediate early gene expression.